Parents’ perception on factors of early marriage among the Urhobos in Delta State of Nigeria - Agege, Emmanuel A.; Nwose, Ezekiel Uba; Odjimogho, Stella (International Journal Of Community Medicine And Public Health, 2018)
Early marriage forces girls into adulthood before they are emotionally and physically matured, and it has harmful effects on their health, educational, economic and social development. In many countries, 18 years is the legal age of marriage and Nigeria has made a constitutional effort to establish same as a minimum age for marriage. This narrative review examined the causes and consequences of early marriage with a view to establish framework to assess the perception on factors among Urhobos in Nigeria. Unpublished stories are appraised alongside news media and published literature to illustrate scenarios that exemplify discussed causes. Several causes of early marriage were noted and gender discrimination, ignorance, and unexpected pregnancy appear salient or are under-discussed. There is evidence that men and women prefer husbands to earn higher wages than wives and females are less ambitious. Although there are public health concerns in the literature, data on perception of parents, especially those in low socioeconomic status, regarding public health is lacking. Critical appraisal posits that early marriage is not only shrouded in legalities, but is also caused by multiple factors. The factors that cause or lead to early marriages need to be identified for each society to appropriately address the associated ramifications. The lack of data on perception of parents suggests that educational intervention needs to start with community needs assessment.